Peran Foundation for Education and Development Terhadap Pekerja Migran Myanmar di Thailand Selatan 2015-2018 Melalui Participation, Empowerment dan Mediator (PEM) - Arisanto, Puguh Toko; Andini Lelemboto, Mega Christy (Global and Policy Journal of International Relations, 2021)
Abstract Thailand is the largest destination country for migrant workers from Myanmar. Migration is carried out because of the necessities of living, work and natural disasters. However, the life of Myanmar migrant workers in Thailand is vulnerable and does not rid of problems as exploitation, violence, discrimination, HIV AIDS, abortion. Moreover, they commonly also work in unskilled sector due to the low level of education and the quality of human resources. FED, an NGO, as a non-state actor comes to assist in solving these problems. FED seeks to support the needs of migrant workers, especially in improving education and human resources. This paper will explain the role of the FED towards Myanmar migrant workers in Thailand in 2015-2018. To analyze it, the writer used the role of NGO theory which consists of participation, empowerment and mediator. The results in the study show that the FED has met three roles as an NGO. The role of participation is manifested in activities that require the activeness of migrant workers through educational programs, especially for children. Second, the concept of empowerment is realized through training programs in an effort to develop the capacity of migrant workers. Lastly is the role as a mediator, namely FED's efforts to bridge the migrant worker with the global community through its programs both through digital and non-digital mediation. Keywords : Migran workers, FED’s roles, Participation, Empowerment, Mediator Abstrak Thailand menjadi negara destinasi terbesar pekerja migran asal Myanmar. Migrasi dilakukan karena faktor kebutuhan hidup, pekerjaan dan bencana alam. Namun kehidupan pekerja migran Myanmar di Thailand rentan dan tidak luput dari permasalahan-permasalahan seperti eksploitasi, kekerasan, diskriminasi, penyakit HIV AIDS, aborsi. Selain itu, mereka umumnya juga bekerja di sektor yang masuk kualifikasi unskilled. Hal ini dikarenakan rendahnya pendidikan dan kualitas sumber daya manusia. FED, sebuah NGO, sebagai aktor non negara hadir untuk membantu dalam penyelesaian masalah tersebut. FED berusaha untuk menyokong kebutuhan pekerja migran khususnya dalam peningkatan pendidikan dan sumber daya manusia. Tulisan ini akan menjelaskan peran FED terhadap pekerja migran Myanmar di Thailand tahun 2015-2018. Untuk menganalisisnya, penulis menggunakan teori peran NGO yang terdiri dari participation, empowerment dan mediator. Hasil dalam penelitian menunjukkan bahwa FED telah menjadi tiga peran sebagai NGO. Peran participation diwujudkan dengan kegiatan-kegiatan yang menuntut keaktifan pekerja migran melalui program-program pendidikan khususnya untuk anak-anak. Kedua, konsep peran empowerment diwujudkan melalui program- program pelatihan dalam upaya pengembangan kemampuan para pekerja migran. Terakhir adalah peran sebagai mediator yaitu upaya FED menjembatani pekerja migran Thailand dengan masyarakat global melalui program-programnya baik melalui mediasi digital maupun non digital. Kata Kunci : Pekerja Migran, Peran FED, Participation, Empowerment, Mediator